2020
DOI: 10.1111/jen.12762
|View full text |Cite
|
Sign up to set email alerts
|

Influence of adult diet on fitness and reproductive traits of the egg parasitoid Anagrus virlai (Hymenoptera: Mymaridae), a potential biocontrol agent against the corn leafhopper

Abstract: Dalbulus maidis is the most important leafhopper pest of maize in the Americas. Anagrus virlai is an egg parasitoid commonly associated with the corn leafhopper. We evaluated whether the performance of A. virlai is dependent on different diets provided during 24 hr or throughout adult female lifetime. Additionally, functional response of A. virlai on D. maidis eggs using maize leaves containing honeydew plus honey was described. A. virlai is a mostly pro‐ovigenic autogenic species whose females are able to par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 39 publications
0
8
0
1
Order By: Relevance
“…In accordance with our findings, these studies also demonstrated that diet positively influenced longevity in females and that, when fed with sugary substances, females lived longer and laid more eggs. Nevertheless, in the case of the highly pro-ovigenic wasp A. virlai, although feeding influenced longevity, it did not significantly affect the fecundity of the females, since they laid almost all of their mature eggs during the first few days of life (Hill et al, 2020).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In accordance with our findings, these studies also demonstrated that diet positively influenced longevity in females and that, when fed with sugary substances, females lived longer and laid more eggs. Nevertheless, in the case of the highly pro-ovigenic wasp A. virlai, although feeding influenced longevity, it did not significantly affect the fecundity of the females, since they laid almost all of their mature eggs during the first few days of life (Hill et al, 2020).…”
Section: Discussionmentioning
confidence: 93%
“…In fact, several species (including species belonging to the genus Cosmocomoidea (formerly Gonatocerus)) display this type of reproductive strategy (Irvin and Hoddle, 2009), evidenced by female emergence with a mature complement of eggs and no further egg maturation recorded. However, exceptions to this observed trend have been documented for some mymarid species: Anaphes iole Girault, A. listronoti Huber (Riddick, 2005;Boivin and Martel, 2012;Boivin and Ellers, 2016) and Anagrus virlai Triapitsyn (Hill et al, 2020) display OIs between 0.70 and 0.90, for which they are considered highly pro-ovigenic, but capable of maturing eggs in addition to their initial egg load.…”
Section: Discussionmentioning
confidence: 94%
“…[69]. On the other hand, in the egg parasitoid Anagrus virlai Triapitsyn (Mymaridae), the number of parasitized eggs decreases as females age, and wasps experience a double egg maturation process [30]. Palottini [62], using a similar experimental design and statistical analysis to the one we employed, found that the egg production rate of Gonatocerus sp.…”
Section: Discussionmentioning
confidence: 99%
“…Parasitoid longevity influences the extent to which parasitoid becomes time-limited. To maximize longevity in the fleld, many parasitoids require a carbohydrate source such as nectar, hemipteran honeydew, or they might feed directly on their hosts [29,30. However, the variability in nutrient income caused by the use of external stochastic sources of nutrients can entail great risks of starvation.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies report that adult diets can change parasitoids' lifetime oviposition patterns (Bai and Smith 1993;Wade et al 2008;Hill et al 2020). This suggests that we may be able to modify parasitoids' lifetime oviposition trajectory by tailoring their adult diets before release to achieve effective augmentative biological control under different circumstances.…”
Section: Introductionmentioning
confidence: 99%